2015
DOI: 10.1007/s00232-015-9821-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erythrodiol, A Natural Pentacyclic Triterpene from Olive Oil, on the Lipid Membrane Properties

Abstract: The effect of erythrodiol, a natural pentacyclic triterpene to which humans are exposed through nutrients, on the lipid membranes is studied using liposomes as a membrane model. Empty and erythrodiol-loaded liposomes were prepared by the reverse phase evaporation method followed by the extrusion and by the thin film hydration method. Liposomes were characterized in terms of size and zeta potential and were imaged by transmission electron microscopy (TEM) and atomic force microscopy (AFM). The effect of erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The triterpenes are bioactive molecules found in olive skin and in the leaves of olive trees. Hydroxyl pentacyclic triterpene acids (HPTA) (oleanolic and maslinic acid) and dialcohols (uvaol and erythrodiol) are responsible for several biological activities attributed to VOO, such as anti‐inflammatory, hepatoprotective, anticancer, antiviral, anti‐HIV, anti‐microbial, antifungal, anti‐diabetic, gastroprotective and hypolipidemic . Recent findings demonstrated also neuroprotective effects exerted by maslinic and oleanolic acid .…”
Section: Virgin Olive Oil Bioactivesmentioning
confidence: 99%
“…The triterpenes are bioactive molecules found in olive skin and in the leaves of olive trees. Hydroxyl pentacyclic triterpene acids (HPTA) (oleanolic and maslinic acid) and dialcohols (uvaol and erythrodiol) are responsible for several biological activities attributed to VOO, such as anti‐inflammatory, hepatoprotective, anticancer, antiviral, anti‐HIV, anti‐microbial, antifungal, anti‐diabetic, gastroprotective and hypolipidemic . Recent findings demonstrated also neuroprotective effects exerted by maslinic and oleanolic acid .…”
Section: Virgin Olive Oil Bioactivesmentioning
confidence: 99%
“…Liposomes have found applications in pharmacology for drug delivery, and in food for the delivery of flavors and nutrients. They are also used as models to study the interaction of chemicals with biological cells (Habib et al 2015). Concerning the encapsulation of contaminants, 1-aminopyrene and 1-hydroxymethylpyrene bind strongly on neutral liposomes composed of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (Macii et al 2019).…”
Section: Liposomesmentioning
confidence: 99%
“…Among the very few studies, it has been reported that pentacyclic TTPs affect the membrane phase properties, alter the CHOL-rich domains, and may affect the function of membrane-associated proteins (Prades et al, 2011). Also, it has been demonstrated that the interaction of ER (Abboud et al, 2016;Habib et al, 2015) and the tetracyclic TTPs like cucurbitacin E (Habib et al, 2013) and corticoids (Abboud et al, 2016(Abboud et al, , 2015Kaddah et al, 2018b) affect the membrane dynamics.…”
Section: Introductionmentioning
confidence: 99%